PENGARUH MODEL PEMBELAJARAN ECOLITERACY DAN ADAPTASI (ELA) TERHADAP KESADARAN MENJAGA LINGKUNGAN - M Irdan Jundi Arrosiyd; Hermawan Wahyu Setiadiy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Environmental awareness among elementary school students is still relatively low, as indicated by their lack of concern for cleanliness and sustainability of the school environment. This condition indicates the need for learning innovations that can foster students' ecological awareness more effectively. This study aims to determine the differences in environmental awareness between students who participate in learning using the Ecoliteracy and Adaptation (ELA) model and students who participate in conventional learning. This study used a quantitative approach with an experimental method. The research subjects consisted of two fifth grade classes at Gedongkuning Public Elementary School, each with 28 students as the experimental class and the control class. Data collection techniques used environmental awareness questionnaires, tests, and observations. Data were analyzed using descriptive statistics and independent sample t-tests on the pretest and posttest results. The results showed that there was an increase in environmental awareness in the experimental class after the implementation of the Ecoliteracy and Adaptation learning model. The average posttest score of students in the experimental class was higher than that of the control class, and the t-test results indicated a significant effect of the use of the ELA model on students' environmental awareness. Thus, the Ecoliteracy and Adaptation learning model is effective in increasing environmental awareness in elementary school students.